Understanding Urban Functionality from POI Space - Fan, Dongwan; Qin, Kun; Kang, Chaogui (2018 26th International Conference on Geoinformatics, 2018)
Urbanization's rapid progress presents an urgent challenge for developing a predictive, quantitative theory to support the comprehensive understanding of the urban built environment. Among, the intertwined relationship between urban functionality and activity diversity has been widely recognized and quantified in terms of the richness of points of interest (POIs). In this research, we provided a novel methodology for revealing the co-occurrences of POIs within the city and the mechanisms of the interplay between them. We built and studied the network of relatedness between POIs, finding that more common POIs are located in a densely connected core whereas rarer and more unique POIs occupy a less-connected periphery. We simulated the diffusion process of the network in different sub-district, finding that common POIs act more on the speed of diffusion, unique POIs act more on the scope of diffusion. This research may help inform stakeholders the proper way of promoting the vitality of the local urban built environment.